Activin receptor-like kinase 7 silencing alleviates cardiomyocyte apoptosis, cardiac fibrosis, and dysfunction in diabetic rats. Issue 16 (August 2022) - Liu, Lin; Zhou, Xin; Zhang, Qiyu; Li, Li; Shang, Yuanyuan; Wang, Zhihao; Zhong, Ming; Chen, Yuguo; Zhang, Wei; Tang, Mengxiong
Activin receptor-like kinase 7 (ALK7) is associated with lipometabolism and insulin sensitivity. Our previous study demonstrated that ALK7 participated in high glucose-induced cardiomyocyte apoptosis. The aim of our study was to investigate whether ALK7 plays an important role in modulating diabetic cardiomyopathy (DCM) and the mechanisms involved. The model of diabetes was induced in male Sprague−Dawley rats (120–140 g) by high-fat diet and intraperitoneal injections of low-dose streptozotocin (30 mg/kg). Animals were separated into four groups: control, DCM, DCM with ALK7 silencing, and DCM with vehicle control. The cardiac function was assessed by catheterization. Histopathologic analyses of collagen content and apoptosis rate, and protein analyses of ALK7, Smad2/3, Akt, Caspase3, and Bax/Bcl2 were performed. This study showed a rat model of DCM with hyperglycemia, severe insulin resistance, left ventricular dysfunction, and structural remodeling. With ALK7 silencing, the apoptotic cell death (apoptosis rate assessed by TUNEL, ratio of Bax/Bcl2 and expression of cleaved Caspase3), fibrosis areas, and Collagen I-to-III ratio decreased significantly. The insulin resistance and diastolic dysfunction were also ameliorated by ALK7 silencing. Furthermore, the depressed phosphorylation of Akt was restored while elevated phosphorylation of Smad2/3 decreased after the silencing of ALK7. The results suggest ALK7 silencing plays a protective role in DCM and may serve as a potential target for the treatment of human DCM.